A COMPARATIVE STUDY OF CONSUMER SATISFACTION WITH REFERENCE TO MOBILE BANKING OF SELECTED URBAN AND RURAL AREAS OF GUJARAT - Jain, Manali; Sharma, Rita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study aims to compare the level of consumer satisfaction with mobile banking services in selected urban and rural areas of Gujarat, India. It hopes to shed light on the current state of mobile banking in Gujarat and identify areas for improvement. The result of this study will provide valuable insights for banks and financial institutions, as well as policymakers, to better understand the needs of their consumer and strive to enhance their mobile banking service. It may reveal disparities in the level of satisfaction between urban and rural areas, which could prompt further action to address the gap and improve financial inclusion.